25-Hydroxyvitamin D Serum Levels Unrelated to Fasting Blood Glucose Levels of Premenopausal Women in Padang - Erasta, Junira; Sulastri, Delmi; Afriwardi (Future Science, 2020)
Introduction: Low serum 25-Hydroxyvitamin D levels in premenopausal women result in the impaired release of insulin from the pancreas and reduce glucose tolerance which causes the body's metabolism to slow down resulting in weight gain leading to insulin resistance and resulting in diabetes mellitus (DM). The incidence of DM occurs at premenopausal ages compared to productive ages, the percentage of women experiencing diabetes is higher than men. This study aims to determine the relationship between 25-Hydroxyvitamin D serum levels and fasting blood glucose (FBG) levels of premenopausal women in Padang. Method: This study was conducted in the city of Padang, is observational, cross-sectional design. The study sample was 62 premenopausal women. Measurement of serum 25-Hydroxyvitamin D levels was measured by enzyme-linked immunosorbent assay and FBG levels were measured by the GOD-PAP method. Data were analyzed using the Pearson correlation test. Results: The average serum level of 25-Hydroxyvitamin D respondents was 30.96 ± 10.96 ng/ml. The average FBG level of respondents was 107.03 ± 13.74 mg/dl. There was no significant relationship between 25-Hydroxyvitamin D serum levels and FBG levels (r = - 0.038, p = 0.769). Conclusion: There is no significant relationship between 25-Hydroxyvitamin D serum levels and FBG levels of premenopausal women in Padang.